Development of Electronics Student Worksheets Based on the Nature of Science in the Organic Chemistry on Polymer Materials Course - Nanda Salwa Aulia; Susilawati Susilawati; Jimmi Copriady (Jurnal Penelitian Pendidikan IPA, 2024)
This research is motivated by the need to provide teaching materials that can help students understand organic chemistry, especially polymer materials. Based on findings in the field, Organic Chemistry is one of the subjects whose material is difficult to understand. The development of the times and technology has brought developments in teaching materials in learning, namely technology-based. The purpose of this study is to produce E-LKM based on Nature of Science in the Organic Chemistry Course on Polymer Materials that can help students understand polymer materials more easily.The method used is the Research and Development (R&D) method, with the ADDIE model, which consists of 5 phases, namely the analysis phase, design phase, development phase, implementation phase and evaluation phase. The Nature of Science-based Electronics Student Worksheets developed on Polymer material was declared valid based on material and media validation with values ​​of 93% and 97% respectively. The Nature of Science-based Electronics Student Worksheets on polymer material that was developed received a very good response from lecturers and students with scores of 92% and 90% respectively. Electronic Student Worksheet was declared valid and received a positive response from users and can be used in classroom learning.